An implementation of hot-swap circuit with high reliability. (June 2020) - Li, Dagang; Li, Zehong; Li, Wei; Fan, Hua; Wang, Ce; Che, Hongrui; Zeng, Xuanhong; Feng, Quanyuan; Heidari, Hadi
Abstract: For the information transmission and application field of the bus, it is necessary to design a bus transceiver with high reliability and hot-swap ability. In order to achieve this requirement, this paper proposes a novel transceiver circuit with hot-swap structure. This structure effectively improves the transistor utilization efficiency and reduces the chip area on the premise of achieving the hot-swap performance. Furthermore, the traditional Schottky diode is avoided, and the hot-swap circuit proposed in this work can be implemented in any CMOS process. A prototype was fabricated in 0.5 μm CMOS technology, and the measurement results match well with the simulation results show that the chip meets the design requirements.